KEPERCAYAAN DALAM TIM - Raharso, Sri (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2011)
Organizations are nowadays faced with a growing number of challenges for their successfuloperation in the current market and society. Their survival in the current turbulent market iscontinuously at risk and becomes uncertain. The competitive challenges of the last decade haveseen an increase in the number of organizations using teams as a new work design. Hence,organizations have become flatter and more team centred. So, a team is the most common andbasic working unit in today’s business organizations. One of the most important elements thatdetermine the ability of teams to cooperate effectively is the ability of each team member to trustthe entire team and each of the other team members. Scholars have long been interested in thestudy of trust in organizations; trust is seen as one of the critical elements. Trust is critical toindividuals, organizations, and society in general. Trust is important because it is linked to thelevel of employee and organizational performance. Organizations that were identified as “hightrust” generally got more qualified applicants, experienced lower turnover, and healthcare costs,higher levels of customer satisfaction, and greater innovation and risk taking. Since breakingtrust gives rise to distrust, maintaining trust requires careful attention from management. Hightrust can account for a company’s competitiveness in the long run.